desechos sólidos y su impacto socioambiental en la población de la parroquia tendales, año 2023 - Capa Tobar, Geremy Steven; Moreno Castillo, Jonathan Patricio (Machala: Universidad Tecnica de Machala, 2024)
It is essential to understand the environmental effects caused by solid waste. In this sense, this degree work focuses on the study of solid waste and its socio-environmental impact on the population of the Tendales´ Parish during the year 2023, characterized by the deterioration in the quality of life of the inhabitants, the lack of knowledge of environmental regulations, lack of awareness and poor implementation of strategies by the competent authorities. Therefore, the general objective of the research determined the socio-environmental impact generated by solid waste; articulated, the specific objectives focused on identifying the environmental problems generated by the inadequate management of solid waste, in the same way there is a tendency to establish the effects on the population, establishing responsibilities and analysis of incorporated strategies for the improvement of the problems identified in the parish. The research was based on a mixed methodological approach since the quantitative and qualitative method was used to carry out surveys and interviews, in which necessary data was obtained from the population and the actions by the authorities, which allowed for a deeper understanding. the problems of the town; while the epistemological approach was empirical-inductive and hypothetical-deductive, this made it possible to evaluate the socio-environmental impact of solid waste management and propose improvement measures focused on environmental education, adequate infrastructure and recycling and waste reduction policies that actively involve the community in the sustainable management of its waste. As a result of the empirical research, through surveys and interviews, it was determined that the accumulation of solid waste has generated a high rate of contamination of water, air and soil, resulting in the erosion of the ecosystem in the Tendales´ parish. constituting an unfavorable socio-environmental factor that increases over time. Furthermore, this problem has had a significant increase, in which there has been a notable increase in diseases and proliferation of pests caused by the presence of remnants, a situation that has worsened despite the implementation of measures such as recycling programs and environmental awareness campaigns, which have not been sufficient to solve this problem. Based on these results, the design of a socio-environmental awareness plan aimed at the sustainable management of solid waste in the Tendales´ parish was established as a proposal, which will be implemented in collaboration with the Municipal and Parish GAD, promoting the active participation of the community in the sustainable management of solid waste. In reference to the proposal, an operational planning was carried out that determined the activities to be carried out with their respective schedule and whose persons responsible for execution are the leaders of the parish, the members of the parish GAD of Tendales and the municipal GAD of the canton of El Guabo. Regarding feasibility, the dimensions for its implementation were analyzed. Technically, it is based on operational resources and the experience of expert trainers in the different topics of environmental awareness campaigns. In addition, the budget for the logistics of human resources, materials and technological equipment corresponding to $3,858.75 was established, being necessary for the effectiveness of the planned activities. Socially, it is feasible due to the benefits that generate positive impacts and citizen awareness. In the environmental dimension it is justified as it is oriented towards the sustainable management of solid waste, ensuring adequate living conditions at the community level.
Es primordial comprender las afectaciones ambientales producidas por los desechos sólidos. En tal sentido, el presente trabajo de titulación se enfoca en el estudio de los Desechos sólidos y su impacto socioambiental en la población de la parroquia Tendales durante el año 2023, caracterizado por el deterioro en la calidad de vida de los habitantes, el desconocimiento de las normativas ambientales, la falta de concientización y la escasa implementación de estrategias por parte de las autoridades competentes. Por lo tanto, el objetivo general de la investigación determinó el impacto socioambiental generado por los desechos sólidos; articuladamente los objetivos específicos se centraron en identificar los problemas ambientales generados por el inadecuado manejo de desechos sólidos, de la misma manera se tiende a establecer las afectaciones en la población, estableciendo responsabilidades y análisis de estrategias incorporadas para el mejoramiento de la problemática identificada en la parroquia. La investigación se fundamentó en un enfoque metodológico mixto puesto que se utilizó el método cuantitativo y cualitativo para la realización de encuestas y entrevistas, en el que se obtuvieron datos necesarios de la población y las acciones por parte de las autoridades, lo que permitió profundizar en la problemática de la localidad; mientras el enfoque epistemológico fue empírico-inductivo e hipotético-deductivo, esto permitió evaluar el impacto socioambiental de la gestión de desechos sólidos y proponer medidas de mejora enfocadas en la educación ambiental, infraestructura adecuada y políticas de reciclaje y reducción de residuos que involucran activamente a la comunidad en la gestión sostenible de sus desechos. Como resultados de la investigación empírica, a través de las encuestas y entrevistas, se determinó que la acumulación de los desechos sólidos ha generado un alto índice de contaminación al agua, aire y suelo, dando como consecuencia el desgaste del ecosistema en la parroquia Tendales, constituyéndose un factor socio ambiental desfavorable que incrementa con el paso del tiempo. Además, esta problemática ha tenido un aumento significativo, en el que se ha evidenciado un notorio incremento de enfermedades y proliferación de plagas causado por la presencia de remanentes, situación que se ha agudizado a pesar de la implementación de medidas como programas de reciclajes y campañas de concientización ambiental, las mismas que no han sido suficientes para solucionar esta problemática. En base a estos resultados, se estableció como propuesta el diseño de un plan de concientización socio ambiental orientado al manejo sostenible de desechos sólidos en la parroquia Tendales”, el cual será implementado en colaboración con el GAD Municipal y Parroquial, impulsando la participación activa de la comunidad en el manejo sostenible de los desechos sólidos. En referencia a la propuesta se realizó una planificación operativa que determinó las actividades a ejecutarse con su respectivo cronograma y cuyos responsables de ejecución son los dirigentes de la parroquia, los miembros del GAD parroquial de Tendales y del GAD municipal del cantón El Guabo. Respecto a la viabilidad se analizaron las dimensiones para su implementación. Técnicamente se fundamenta en recursos operativos y la experiencia de los capacitadores expertos en las diferentes temáticas de las campañas de concientización ambiental. Además, se estableció el presupuesto para la logística de recursos humanos, materiales y equipos tecnológicos correspondiente a $3.858,75, siendo necesario para la efectividad de las actividades planificadas. En lo social es factible por los beneficios que generan impactos positivos y concientización ciudadana. En la dimensión ambiental se justifica por cuanto se orienta al manejo sostenible de los desechos sólidos, asegurando las condiciones de vida adecuadas en el ámbito comunitario.
Keywords: DESECHOS SOLIDOS; PROBLEMAS AMBIENTALES; IMPACTO SOCIO-AMBIENTAL; MEDIO AMBIENTE; TENDALES